2016
DOI: 10.1021/acs.joc.5b02845
|View full text |Cite
|
Sign up to set email alerts
|

Stereo-, Regio-, and Chemoselective [3 + 2]-Cycloaddition of (2E,4E)-Ethyl 5-(Phenylsulfonyl)penta-2,4-dienoate with Various Azomethine Ylides, Nitrones, and Nitrile Oxides: Synthesis of Pyrrolidine, Isoxazolidine, and Isoxazoline Derivatives and a Computational Study

Abstract: One-pot chemo-, regio-, and stereoselective synthesis of series of heterocyclic and spiroheterocyclic compounds was accomplished through mono- and bis[3 + 2]-cycloaddition reactions of (2E,4E)-ethyl 5-(phenylsulfonyl)penta-2,4-dienoate as a dipolarophile with azomethine ylides, nitrones, and nitrile oxides in good yields. The structures of the products were established by spectroscopic techniques as well as by single-crystal XRD study, and DFT calculations were performed to further understand the mechanism of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…The reaction mechanisms of the 32CA reactions of NOs with ethylene and acetylene derivatives, as well as the study of the regioselectivity in the formation of the two isoxazolines, have been widely analysed within the Density Functional Theory (DFT) framework . Fulminic acid 2 , the simplest NO, presents a high activation enthalpy toward ethylene 10 , 13.3 kcal·mol −1 , and toward acetylene 11 , 13.7 kcal·mol −1 …”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanisms of the 32CA reactions of NOs with ethylene and acetylene derivatives, as well as the study of the regioselectivity in the formation of the two isoxazolines, have been widely analysed within the Density Functional Theory (DFT) framework . Fulminic acid 2 , the simplest NO, presents a high activation enthalpy toward ethylene 10 , 13.3 kcal·mol −1 , and toward acetylene 11 , 13.7 kcal·mol −1 …”
Section: Introductionmentioning
confidence: 99%
“…Subramanian et al 27 have shown that the chemoselectivity of the cycloaddition of azomethine ylides to (2E,4E)ethyl 5-(phenylsulfonyl)penta-2,4-dienoate (65) for the synthesis of spiropyrrolidines 66 (24-78% yields) was dependent upon the nature of the dipole as well as its steric bulk (Scheme 21). In the case of nitrile oxides, the cycloaddition occurred at the acrylate double bond.…”
Section: Scheme 20 13-dipolar Cycloaddition Reaction Of Curcumin (63mentioning
confidence: 99%
“…1,3-Dipolar cycloaddition (1,3-DC) of stabilized azomethine ylides based on ninhydrin and α-amino acids to activated alkenes or alkynes represents a concise and the most convenient method for the regio- and stereoselective synthesis of spiropyrroli­(zi)­dine and spiropyrroli­(zi)­ne ring systems . Usually, ninhydrin-derived ylides are generated in situ and used in the reaction without isolation.…”
Section: Introductionmentioning
confidence: 99%